The impact of work-related stress on medication errors in Eastern Region Saudi Arabia. (7th May 2018) - Salam, Abdul; Segal, David M; Abu-Helalah, Munir Ahmad; Gutierrez, Mary Lou; Joosub, Imran; Ahmed, Wasim; Bibi, Rubina; Clarke, Elizabeth; Qarni, Ali Ahmed Al
Abstract: Objective: To examine the relationship between overall level and source-specific work-related stressors on medication errors rate. Design: A cross-sectional study examined the relationship between overall levels of stress, 25 source-specific work-related stressors and medication error rate based on documented incident reports in Saudi Arabia (SA) hospital, using secondary databases. Setting: King Abdulaziz Hospital in Al-Ahsa, Eastern Region, SA. Participants: Two hundred and sixty-nine healthcare professionals (HCPs). Main Outcome Measures: The odds ratio (OR) and corresponding 95% confidence interval (CI) for HCPs documented incident report medication errors and self-reported sources of Job Stress Survey. Results: Multiple logistic regression analysis identified source-specific work-related stress as significantly associated with HCPs who made at least one medication error per month ( P < 0.05), including disruption to home life, pressure to meet deadlines, difficulties with colleagues, excessive workload, income over 10 000 riyals and compulsory night/weekend call duties either some or all of the time. Although not statistically significant, HCPs who reported overall stress were two times more likely to make at least one medication error per month than non-stressed HCPs (OR: 1.95, P = 0.081). Conclusion: This is the first study to use documented incident reports for medication errors rather than self-report to evaluate the level of stress-related medication errors in SA HCPs. Job demands, such as social stressors (home life disruption, difficulties with colleagues), time pressures, structural determinants (compulsory night/weekend call duties) and higher income, were significantly associated with medication errors whereas overall stress revealed a 2-fold higher trend.